Finding the undiagnosed: a qualitative exploration of hepatitis C diagnosis delay in the United Kingdom. Issue 6 (29th February 2016) - Harris, M.; Ward, E.; Gore, C.
Summary: Hepatitis C virus (HCV)‐related morbidity and mortality will continue to rise unless HCV testing and treatment uptake increases. In the European region, an estimated nine million people live with HCV, yet only 10–40% are diagnosed. Over 100 000 undiagnosed people live with HCV in the United Kingdom (UK). For some, a late diagnosis can come too late. The aim of this qualitative study was to explore the context of a diagnosis delay among people living with HCV in the UK. Participants were recruited through two London Hospitals and The Hepatitis C Trust. Eligible participants identified a recent (<3 years) HCV diagnosis and a historical HCV transmission risk period (>15 years). The primary method of data collection was in‐depth interviews (12 participants) and focus groups (16 participants). Analysis was informed by grounded theory principles. The sample, 17 men and 11 women, reported an average gap of 28 years between their HCV‐risk period and first HCV test. Forty per cent had cirrhosis at HCV diagnosis. Diagnosis delay was attributed to limited HCV relevance, felt wellness, stigma, compartmentalization of former injecting practices, unexplained symptoms and general practitioner inaction. Diagnosis context involved a change of health care providers or a chance medical encounter. Trust in providers was impacted by a delayed diagnosis, with implications for future engagement in care. These data indicate that risk awareness does not necessarily result in action. A multipronged approach is needed to increase HCV case finding in the UK, particularly among 'hidden populations' such as former injectors and transfusion recipients.